(untitled) (Fiep Bulletin - online, 2012)
According to the World Health Organization (WHO), disability is an abnormality of structure or appearance of the human body and the functioning of an organ or system, regardless of their cause, as it is in principle a kind of organic disorder. It may be mentioned that the consequences of disability are under a disability and functional activity of the individual, thereby representing a disturbance on a personal level. Disadvantages are the limitations experienced by the individual as a result of impairment and disability, reflecting, therefore, the individual’s relationships with the environment, as well as their adaptation to it. The present study analyzed the profile of people with congenital disability-athlete, attended the Special Advisor to the Disability Support the Municipality of Juiz de Fora / MG (EDPS), identifying age, sex, category of activity and weekly. In this study conducted a qualitative descriptive research with emphasis. The sample consisted of 18 congenitally disabled of both sexes with a mean age 33 ± 13.14 years, enrolled in the EDPS. The research took place during the re-registration of free passes for urban transport in the Special Advisory Support Disabled Municipality of Juiz de Fora / MG (EDPS), which was applied a semi-structured interview. Statistical data from this study are related to gender and patterns of physical activity. It is concluded that people with congenital disabilities are not in total inactivity, practice low-impact activities, with the exception of football.